Head impact accelerations and punch accumulation of female elite amateur - Callan, J.; Watchorn, J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Repeated head impact accumulation may provide a marker of athlete welfare and training prescription in combat and contact sports. Instrumented mouthguards (IMGs) may provide insightful and detailed information to inform sparring, training and athlete monitoring. IMG data from elite boxing competition is currently limited. This case study presents the head impact data from an elite amateur female boxer. METHODS: One elite female boxer (age = 26 years; mass = 70kg; stature = 173cm) took part in an international amateur boxing tournament (3 bouts = 3 x 2 mins:1 min recovery) whilst equipped with a Protecht IMG (OPRO+ smart mouthguard, UK) during each bout. The participant won all three bouts. Variables measured were linear head acceleration (g), angular head acceleration (rad*s), and number of head impacts. One-way ANOVAs (p*0.05) with omega squared (*2) effect size using JASP 0.18.1 were used to compare the following between bouts: mean g; mean rad*s; mean g split by 50th%, 75th% and 90th%; mean rad*s split by 50th%, 75th% and 90th%. RESULTS: Bout 1: total impacts = 117; linear acceleration = 15.7±10.6g; angular acceleration = 3,802±3,272rad*s. Bout 2: total impacts = 58; linear acceleration = 14.6±9.1g; angular acceleration = 3,585±3,863rad*s; Bout 3: total impacts = 57; linear acceleration = 13.1±6.8g; angular acceleration = 3,251±2,244rad*s. There were no significant differences in mean g or rad*s between bouts. There were differences in mean g in the 75th% (p = 0.04, *2 = 0.07; bout 1 = 29.9±12.1g .v. bout 3 = 22.1±6.2g, post hoc p = 0.03) and in the 90th% (p = 0.2, *2 = 0.23; bout 1 = 41.5±10.5g .v. bout 3 = 29.1±4.2g, post hoc p = 0.02) between bouts. There were no differences in mean rad*s between bouts split by %. CONCLUSION: This participant experienced head accelerations lower than those reported from male combat sport and American football athletes [1]. The frequency of head impacts and the magnitude of linear accelerations reduced over the course of the three bouts, with no change in angular acceleration. These data provide novel information regarding head impacts in elite amateur female boxers. Future cohort studies for both sexes are required to better understand the effects of boxing competition.